Analysis of Λb → Λl+ l− rare decays in a non-universal Z′ model. (August 2017) - Banerjee, D.; Sahoo, S.
Abstract: We investigate the rare baryonic Λb → Λl + l − decays in a non-universal Z′ model, which is one of the well-motivated extensions of the standard model (SM). Considering the effects of Z′-mediated flavour-changing neutral currents (FCNCs) we analyse the differential decay rate, forward-backward asymmetries and lepton polarisation asymmetries for the Λb → Λl + l − decays. We find significant deviations from their SM predictions, which could indicate new physics arising from the Z′ gauge boson.